2019
DOI: 10.1080/21655979.2019.1673937
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering of anaerobic digestion for volatile fatty acids, hydrogen or methane production: A critical review

Abstract: Anaerobic digestion (AD) is a well-established technology used for producing biogas or biomethane alongside the slurry used as biofertilizer. However, using a variety of wastes and residuals as substrate and mixed cultures in the bioreactor makes AD as one of the most complicated biochemical processes employing hydrolytic, acidogenic, hydrogen-producing, acetate-forming bacteria as well as acetoclastic and hydrogenoclastic methanogens. Hydrogen and volatile fatty acids (VFAs) including acetic, propionic, isobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
150
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 424 publications
(154 citation statements)
references
References 161 publications
(229 reference statements)
1
150
0
3
Order By: Relevance
“…The average composition of the VFAs was as follows: acetic acid 42.63%, propionic acid 17.29%, iso-butyric acid 1.89%, butyric acid 19.55%, isovaleric acid 15.26%, and valeric acid 3.34% of total VFAs. The composition of the VFAs is linked to the microbial structure in the bioreactor and the established microbial pathways [8]. In the prevailing operating conditions, the dominating bacteria community seemed to favor the biosynthesis of mainly acetic, butyric, and isovaleric acids.…”
Section: Vfas Production Using Immersed Membrane Bioreactormentioning
confidence: 99%
See 2 more Smart Citations
“…The average composition of the VFAs was as follows: acetic acid 42.63%, propionic acid 17.29%, iso-butyric acid 1.89%, butyric acid 19.55%, isovaleric acid 15.26%, and valeric acid 3.34% of total VFAs. The composition of the VFAs is linked to the microbial structure in the bioreactor and the established microbial pathways [8]. In the prevailing operating conditions, the dominating bacteria community seemed to favor the biosynthesis of mainly acetic, butyric, and isovaleric acids.…”
Section: Vfas Production Using Immersed Membrane Bioreactormentioning
confidence: 99%
“…These compounds can be further converted into several high-value products, such as bioplastics, butanol and biodiesel [9]. The VFAs, such as acetic, butyric, and propionic acids, produced through AD, can be used directly or indirectly as chemical building blocks in, for instance, textile and plastic production industries [8]. Along with VFAs, hydrogen is produced during acidogenesis, which has attracted great attention as a clean energy source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to increase the hydrolysis rate, as stated, was introducing the pretreatment method. To date plenty of studies focused on the pretreatment to enhance the digestion performance [8][9][10], few researches were reported for the influence of the pretreatment method on the MEC in terms of sludge [11,12]. Our previous study [12] demonstrated the efficiency of alkaline pretreatment for DS as this process affected soluble organic matter content and microbial community structures during electrogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Acid-producing strains produce volatile fatty acids (VFA), hydrogen (H 2 ) gas and carbon dioxide (CO 2 ) gas from complicated organic molecules via fermentation reactions [1,2]. In fermentation, dark fermentation presents an effective pathway to obtain valuable chemicals from organic waste [3,4].…”
Section: Introductionmentioning
confidence: 99%